Lonely Power : Why Russia Has Failed to Become the West and the West is Weary of Russia - Shevt︠s︡ova, Lilii︠a︡, 1951- (Book collections on Project MUSE., 2010)
Rejection of political reform in Russia risks the gradual decay of the country or even state collapse. Russia can break this vicious circle only if it rejects personalized power and if the West helps Russia transform economically and politically. --Book Jacket.